Use of Numicon in Early Childhood Education with students with Special Educational Needs - Paula Díaz-Serrano; Mónica Arnal-Palacián (Universidade Federal do Oeste da Bahia, 2020)
In today´s society, new school models where the center of all learning is the student, are beginning to be more important. The inclusive school models seek an education that is as equalitarian as possible, avoiding any type of discrimination for showing abilities that are different from what is culturally established. Through a qualitative action research methodology, this article tries to include in the teaching-learning process the use of Numicon manipulative materials that facilitate the individual adaptation of each learning for those who have Special Educational Needs. Thanks to the use of these materials in the classroom, an increase in the development of the critical thinking process has been observed, as well as a greater predisposition on the part of the students towards the development of mathematics and an increase in teamwork.